MTOR inhibition suppresses established epilepsy in a mouse model of cortical dysplasia. (6th March 2015) - Nguyen, Lena H.; Brewster, Amy L.; Clark, Madeline E.; Regnier‐Golanov, Angelique; Sunnen, C. Nicole; Patil, Vinit V.; D'Arcangelo, Gabriella; Anderson, Anne E.
Summary Objective Hyperactivation of the mechanistic target of rapamycin (mTOR; also known as mammalian target of rapamycin) pathway has been demonstrated in human cortical dysplasia (CD) as well as in animal models of epilepsy. Although inhibition of mTOR signaling early in epileptogenesis suppressed epileptiform activity in the neuron subset‐specific Pten knockout (NS‐Pten KO) mouse model of CD, the effects of mTOR inhibition after epilepsy is fully established were not previously examined in this model. Here, we investigated whether mTOR inhibition suppresses epileptiform activity and other neuropathological correlates in adult NS‐Pten KO mice with severe and well‐established epilepsy. Methods The progression of epileptiform activity, mTOR pathway dysregulation, and associated neuropathology with age in NS‐Pten KO mice were evaluated using video–electroencephalography (EEG) recordings, Western blotting, and immunohistochemistry. A cohort of NS‐Pten KO mice was treated with the mTOR inhibitor rapamycin (10 mg/kg i.p., 5 days/week) starting at postnatal week 9 and video–EEG monitored for epileptiform activity. Western blotting and immunohistochemistry were performed to evaluate the effects of rapamycin on the associated pathology. Results Epileptiform activity worsened with age in NS‐Pten KO mice, with parallel increases in the extent of hippocampal mTOR complex 1 and 2 (mTORC1 and mTORC2, respectively) dysregulation and progressive astrogliosis and microgliosis. Rapamycin treatment suppressed epileptiform activity, improved baseline EEG activity, and increased survival in severely epileptic NS‐Pten KO mice. At the molecular level, rapamycin treatment was associated with a reduction in both mTORC1 and mTORC2 signaling and decreased astrogliosis and microgliosis. Significance These findings reveal a wide temporal window for successful therapeutic intervention with rapamycin in the NS‐Pten KO mouse model, and they support mTOR inhibition as a candidate therapy for established, late‐stage epilepsy associated with CD and genetic dysregulation of the mTOR pathway.